P-152 Does a 24/7 hospice at home service prevent or postpone acute hospital admissions?. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Clarke, Jo; Varvel, Sue
Abstract : Background: Most people wish to die at home but in England almost 50% die in hospital, suggesting that more can be done to keep people at home. Some studies have shown this may be possible, especially with adequate support and good pain control. Methods: Rennie Grove Hospice Care (RGHC) carried out an independent study to identify the value of their night team in providing 24/7 care over a period of 145 nights. The study considered whether the provision of overnight care affected decisions to make hospital admissions. Data from a night nurse template recording all overnight visits, a review of 42 patient/carer records of those who had called the night team, a carer questionnaire (n=87), carer interviews (n=18) and staff interviews (n=9), were analysed. Results: The night nurse template recorded five overnight admissions made during the study period, all for acute reasons and considered unavoidable. Review of 42 patient records showed 23 hospital/hospice admissions occurred, most during the daytime (18 to hospital, five to a hospice) of which only three were considered avoidable. The carer questionnaires showed 13 (16%) of their cared-for persons had been admitted to hospital in the last few weeks of life, with most reporting the admission was necessary. Staff interviews identified a pride in supporting patients to stay at home, while information from carers gave a clear indication that RGHC nurses enabled their cared-for individual to remain at home; that contact with the night team helped prevent or postpone an admission; and without RGHC their alternative would have been 111/999, district nurse or out-of-hours GP. Conclusions: There are occasions when hospital admission is appropriate. However, there was clear evidence showing support from the night team could prevent or postpone hospital admissions.